Strengthening the research–practice loop in applied animal behavior: Introduction to the special issue. Issue 2 (26th August 2022) - Alligood, Christina; Edwards, Timothy; Mahoney, Amanda
Abstract : Though operant learning has been applied to socially significant animal behavior for many years, connections between these practical applications and the basic science that supports them have weakened over time. There is a need for replications and extensions of technologies derived from basic research to applied animal settings, and for practical questions to be taken back to the lab where they can be modeled and studied under controlled conditions before incorporating the results in applied behavior‐change research and practice. This special issue highlights ways that behavior analysis can contribute to and support the development of evidence‐based applications with animals. Articles in this issue provide context for the relationship between basic research and practice in animal behavior, apply basic principles to animal behavior practice, and investigate practical problems using basic research techniques. Each of these is important for a robust interchange between basic science and practice. Here we comment on the contributions of each article to the literature and identify directions for future research.